Atopic Dermatitis: Relationship Of Risk Factors On Children With Atopic Dermatitis.: A Literature Review - Athirah, Fatin Nisrina; Tedjaprasadja, Leonardo (Faculty of Medical - UPN Veteran Jawa Timur, 2024)
AbstractBackground: Atopic dermatitis (AD) is a persistent and recurring inflammatory skin condition, marked by acute eczema or chronic lichenified lesions, with a diverse range of presentations. This skin disease affects almost 10-20% of people worldwide. The progression of atopic dermatitis is characterized by chronic relapses, which can greatly impact patients' quality of life. Biomarkers have long played an essential role in various medical applications, particularly for diagnostic purposes. However, identifying appropriate biomarkers for atopic dermatitis remains challenging, primarily due to difficulties in obtaining samples. Objective: To find out the antiderm mobile-based application, discussing the knowledge of atopic dermatitis. Method: Literature review is taken from databases such as PubMed and Google Scholar published in the last 5 years, namely from 2018-2022. Then find out about the ANTIDERM mobile-based application. Results: Based on the literature, there are several biomarkers that can be used for patients with atopic dermatitis including TARC or CCL17, CCL27, phytosphingosine CD300a, Interleukin-1 family (IL-18, IL1?, CXCL8), adipokines, FABP5, filaggrin. In addition, the mobileantiderm-based application facilitates communication between doctors and patients, and contains some information about the symptoms of dermatitis so that the public can know the symptoms of dermatitis and how to avoid this dangerous disease. Conclusion: From this literature, it was found that there are several current methods for patients with atopic dermatitis that can be used to help the community in preventing atopic dermatitis. Keywords: Biomarker Atopic Dermatitis, Atopic Dermatitis Diagnosis, Mobile Health Applications Atopic Dermatitis